Cyclotron: a secure, isolated, virtual cycle-scavenging grid in the enterprise - Kane, Kevin; Dillaway, Blair (Proceedings of the 6th International Workshop on Middleware for Grid Computing, 2008)
Cycle-scavenging grids appeal to organizations with large numbers of workstations that remain idle outside of working hours as potential sources of grid computing cycles, but security and isolation issues that come with the use of non-dedicated resources have slowed their adoption in the enterprise. In this paper we present Cyclotron, a prototype cycle-scavenging grid solution that leverages virtualization and a declarative policy-based access control infrastructure supporting flexible authorization rules and the constrained delegation of access rights to address these requirements.